Characterization of a terpene synthase activity in Castellaniella defragrans - Elisabeth Engler-Hüsch (2017)
Monoterpenes are hydrocarbons with multiple beneficial properties, for instance antimicrobial effects. The interest in monoterpenes for the pharmaceutical use has increased over the last decades. Monoterpenes synthases can catalyze the formation of various monoterpenes due to highly active carbocation intermediates. The β-proteobacterium Castellaniella defragrans 65Phen is capable of using monoterpenes as sole carbon and energy source under anaerobic denitrifying conditions. A new degradation pathway for the acyclic monoterpenes β-myrcene and geraniol was ascertained, revealing a novel enzyme, the linalool dehydratase/isomerase. A deletion mutant lacking this enzyme did grow on (R,S)-linalool under formation of the two monocyclic monoterpenes α-terpinene and terpinolene as metabolites. This had led to the suggestion of another metabolism pathway in Castellaniella defragrans 65Phen, involving hitherto unknown enzymes. In this thesis biomass of Castellaniella defragrans 65Phen Δldi from several multi-fed batch cultivations grown on linalool and nitrate was used to develop an improved purification approach by a combination of anion exchange chromatography and size exclusion chromatography. This combination yielded high enzyme purities with few protein bands observable on denaturing gels. The enzyme of interest was further characterized, revealing an optimal pH range from pH 6,0 to pH 9,0 and an optimal temperature of 37 °C for enzyme activity. Previous studies did suggest a single enzyme to be involved in the transformation, while size exclusion chromatography during this study revealed two enzymes of different molecular sizes, a 114 kDa enzyme for synthesis of α-terpinene and a 72 kDa enzyme for synthesis of terpinolene. Furthermore, an increase in size up to 144 ± 11 kDa was observed for the partially purified terpinolene synthase, leading to the suggestion of a multi-enzyme complex formation during anion exchange chromatography. A potential protein band at 55 kDa on a denaturing gel was hypothesized to be the one responsible for terpinolene synthase activity.
Keywords: Castellaniella defragrans